Adsorption of phenol and resorcinol from aqueous solution by Chitosan/Poly(acrylamide–co-2-acrylamido-2-methyl–1- propanesulfonicacid) hydrogels: modeling and kinetic studies - 1C. Raja Kumar, 1Y. Nagaiah, 2K.N. Shashi Kumar,1T.Veera Reddy, Y.Vijaya (International Journal of Advanced Science and Technology, 2020)
The removal of phenol and resorcinol from aqueous solutions by the Chitosan/ Poly(acrylamide-co-2-acrylamido-2-methyl-1-propanesulfonicacid (CPAA) hydrogels has been investigated considering technique of batch mode adsorption. In this study chelating hydrogels are synthesized from Chitosan, acrylamide,2-acrylamido-2-methyl-1-propanesulfonicacid by free radical polymerization method in the presence of N,N-methylene-bis-acrylamide and potassium persulphate act as a cross-linker and initiator. The resulting chelating hydrogels were characterized by Fourier transform infrared spectroscopy (FTIR) and Scanning electron microscopy (SEM). Swelling properties of CPAA hydrogels were also studied. In a batch adsorption system as a function of pH, contact time, adsorbent dose and initial concentration of phenol and resorcinol were investigated comprehensively; thereby the adsorption kinetics and adsorption isotherms are discussed systematically. The adsorption process followed pseudo-second order kinetic model. The analyzed data was correlated with Langmuir and Freundlich isotherm models, where in Langmuir model of adsorption best explained the adsorption process by the CPAA hydrogels. The adsorption capacity of CPAA hydrogels calculated from the Langmuir model was found to be 76.92 mg/g and 83.33mg/g for phenol and resorcinol respectively.